(untitled) (Ibrahim Cardiac Medical Journal, 2012)
Objective: The present study was conducted to study the changes in serum levels of thyroid hormones and thyroid stimulating hormone (TSH) in different trimesters of normal pregnancy. Methods: This cross-sectional study was conducted in the Department of Physiology, Rangpur Medical College Hospital over a period 1 year from July 2008 to June 2009. Apparently healthy pregnant women aged between 20 - 35 years were consecutively included in the study. Patients suffering from thyroid disorders or any other systemic diseases and lactating mothers were excluded from the study. A total of 100 subjects - 75 pregnant women (25 selected from each trimester of pregnancy) and 25 non-pregnant women were purposively selected as case and control groups respectively. Result: The mean age was almost identically distributed between the two groups (23.8 ± 3.9 vs. 24.9 ±4.6, p = 0.343). Lower class patient was predominant in case and control group (68% vs. 64%, p =0.756). The mean serum T3 level was higher in case group compared to control group. The mean serum T3 level was identically distributed in 1st and 3rd trimester (p = 0.536 and p = 0.145 respectively) but significant difference was found in 2nd trimester (p = 0.001). The mean serum T4 level of control group did not experience any change throughout the whole observation period. The serum T4 level was 210 nmol/L at 1st trimester then it began to increase almost a plateau at 2nd trimester and then gradually dropped 232.2 nmol/L at third trimester. The mean serum TSH level was 1.1 mIU/L at 1st trimester then it began to increase sharply assumed a mean score 1.3 mIU/L at 2nd trimester. From 2nd trimester onwards it began to decrease upto the end of observation when no change in the non-pregnant women in 1st, 2nd & 3rd trimester. Conclusion: Thyroid hormones (T3, T4) increase in the 2nd trimester of pregnancy and fall again in the 3rdtrimester but TSH does not experience any significant change throughout the pregnancy. Ibrahim Cardiac Med J 2012; 2(2): 19-23